Answer:
1
Step-by-step explanation:
The square of the value in the empty space is the constant in the expanded expression. That is ...
[ ]² = 1
The value in the space is ...
[ ] = √1 = 1
The filled-in equation is ...
(3x -1)² = 9x² -6x +1
_____
The expansion of the square of a binomial is ...
(ax -b)² = a²x² -2abx +b²
Above, we used the constant term to find 'b', but we could also have used the linear term:
-6x = -2(3)bx . . . . . a=3 in this problem
1 = b . . . . . . . divide by -6x
I dont know if this is right but I got: (6x+1)/4
A= 30ft, because you only have to multiply LxW= A that is equal to 2x15=30ft
Answer:
The circumference of a circle can be found by multiplying pi ( π = 3.14 ) by the diameter of the circle. ... Use 3.14 for pi